PRESERVASI KEARIFAN LOKAL NASKAH PARARATON KEN AROK DAN KEN DEDES: STUDI NASKAH PADA NOVEL AROK DEDES - Kurnia, Larasati; Christiani, Lydia (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
The research purpose is to understanding and analyzes the preservation of local wisdom values inside novel Arok Dedes representation. The method used in this research is qualitative, with discourse analysis as a data analysis method. Its results showed that Arok Dedes novel is a new document production from an old document, Pararaton manuscript. The activity document production from Pararaton manuscript to the novel Arok Dedes is an effort to preserve the local content in Pararaton manuscript because it considers the tastes of a global society. The process of preservation local content in Pararaton manuscript showed several stages, the stages are recognition and identification, validation, recording and documentation, storage, transfer, and dissemination. Through the local content preservation stage, the value of local wisdom which is implicit in moral messages in Pararaton manuscript can be described in novel Arok Dedes, so the wisdom values with implicit moral messages in Ken Arok and Ken Dedes folklore can be sustained from generation to generation.